Restructuring Health Reform, Mexican Style - Michael R. Reich (Taylor & Francis Group, 2020)
Mexico's health system is undergoing major restructuring by the administration of President Andrés Manuel López Obrador (known as AMLO) starting in December 2018. The government has eliminated the 2003 health reform (Seguro Popular) from national laws and government agencies and is returning Mexico to a centralized health system with integrated public financing and delivery and reduced private participation. This article looks at the political drivers of Mexico's restructuring reform. Three main ethical principles are identified as the foundation for the government's health system vision: universality, free services, and anti-corruption. The article then compares what existed under Seguro Popular with the new system under the Instituto de Salud para el Bienestar (INSABI), which began on 1 January 2020. The analysis uses the five policy levers that shape health system performance: financing, payment, organization, regulation, and persuasion. The article concludes with five lessons about the reform process in Mexico. First, undoing past reforms is much easier than implementing a new system. Second, the AMLO government's restructuring emerged more from broad ethical principles than detailed technical analyses, with limited plans for evaluation. Third, the overarching values of the AMLO government reflect a pro-statist and anti-market bias, swimming against the global flow of health policy trends to include the private sector in reforming health systems. Fourth, the experiences in Mexico show that path dependence does not always work as expected in policy reform. Finally, the debate of Seguro Popular versus INSABI shows the influence of personality politics and polarization.